The effects of active acupuncture and placebo acupuncture on insomnia patients: a randomized controlled trial. Issue 10 (25th November 2020) - Zhang, Leixiao; Tang, Yu; Hui, Ruting; Zheng, Hui; Deng, Yanli; Shi, Yunzhou; Xiao, Xianjun; Zheng, Qianhua; Zhou, Siyuan; Yu, Siyi; Cao, Wei; Liu, Yin; et al.
ABSTRACT: The purpose of this study was to observe and compare the clinical efficacy of active acupuncture and placebo acupuncture in the treatment of insomnia and mood disorders. 96 patients with insomnia in Chengdu were randomly divided into two groups (1:1). The active acupuncture group (AA group n = 48) received the tube of Park sham device with deep needle insertion. The placebo acupuncture group (PA group n = 48) received the tube of Park sham device with a retractable needle shaft and a blunt tip. The same acupuncture points and treatment cycles were used in both groups. The overall score for the Pittsburgh Sleep Quality Index (PSQI) is the primary outcome. Secondary outcomes recorded sleep rate, self-reported depression scale (SDS), self-assessment anxiety scale (SAS), the 'six component' scores of PSQI, and 'Deqi' scale scores. Eventually, 90 patients completed the study. After 2 weeks of treatment, the total score of PSQI in the AA group was 4.6 ± 2.4 and in the PA group was 12.9 ± 1.8 ( ES  = 3.91, p < .1). The SAS, SDS score in the AA group were 39.9 ± 5.6/39.9 ± 5.9 and in the PA group were 59.7 ± 6.1/61.2 ± 4.4 ( ES  = 3.38/4.9, p < .1). The sleep rate were 93.8% and 25.0% ( p < .1). During the 1 month follow-up period, the PSQI total score in the AA group (5.2 ± 1.9) was superior to the PA group (13.1 ± 1.8) ( ES  = 4.27, p < .1). The SAS, SDS score in the AA group were 40.4 ± 5.1/42.7 ± 6.6 and in the PA group were 63.7 ± 6.6/63.5 ± 4.8 ( ES  = 3.95/3.60, p < .1). Throughout the study period, the 'six component' scores of PSQI in the AA group was superior to the PA group (each p < .1). Except for tingling and cooling, other acupuncture sensations were significant differences (each p < .1). Compared to the placebo acupuncture, active acupuncture can significantly improve insomnia, and clinical efficacy is maintained for at least 6 weeks.